Avaliação da atitude do estudante de medicina a respeito da relação médico-paciente: comparação entre uma escola médica com modelo curricular doaprendizado baseado em problemas e outra com modelo curricular tradicional - Jose Maria Peixoto (2009)
This study presents two articles that aim to examine the attitudes of medical students towards the doctor-patient relationship in two medical schools of a private university that adopt traditional and problem-based learning curricula, respectively. The attitudes were measured by means of the Patient-Practitioner Orientation Scale (PPOS), a validated measureof patient-centered beliefs, with its two sub-scales sharing (focusing on power and control) and caring (focusing on the value of warmth and support). A Portuguese translation of the scale was administered along with a socio-demographic questionnaire to medical students in their second, fifth and tenth semesters of medical school. The first article examined the attitudes towards the doctor-patient relationship in a medical school that adopts PBL curriculum. A total of 132 students (71.74%) completed data collection after informed consent. For the entire cohort, total PPOS score was significantly higher (p < 0.01) for thefemale gender, meaning more patient-centered attitudes among female students. Analysis of sharing and caring subscales scores also showed significantly higher sharing scores among female students, meaning more patient-centered attitudes. Total PPOS score did notchange from the second to the tenth semester, but there was an increase of caring subscale score among male students with no significant difference of total PPOS and its subscales scores among male and female students at tenth semester. There also were no significantassociations between socio-demographic variables and total PPOS and its subscales scores in any of the assessed semesters. These results are similar to those reported in a public medical school of Brazil and other foreign medical schools with traditional curriculum. The secondarticle compared medical students attitudes towards doctor-patient relationship between two medical schools of a private university, one with traditional (TC) and the other with problembased learning (PBL) curricula, respectively. A Portuguese translation of PPOS was administered along with a socio-demographic questionnaire to medical students in theirsecond, fifth and tenth semesters from two medical schools of a private university, one with traditional (TC) and the other with problem-based learning (PBL) curricula, respectively. A total of 274 medical students completed data collection, 132 from the PBL medical school and142 from TC medical school (71.74% and 32.8% of the total number of students in the 2nd, 5th and 10th semester in both schools, respectively). Total PPOS scores were 4.62 (± 0.46 SD) and 4.45 (± 0.43 SD) for the PBL and TC medical schools, respectively (p=0,002), meaning more patient-centered attitudes in the PBL medical school. Total PPOS scores between the two medical schools did not show any significant differences in the 2nd semester but were significantly higher in the PBL medical school in the 5th (p=0,037) and 10th semesters (p=0,036). Changes of total PPOS scores among male and female students with the yearsshowed that male students of both schools had similar scores at the beginning of the course with scores maintenance in TC medical school and significant increase in the PBL medical school at the 10th semester (p=0,023). Total PPOS scores showed a small increase with the years among female students from the TC medical school. In comparison to male medical students, sharing sub-scale score was significantly higher among female students from PBL medical schools, meaning morewillingness to share decisions with patients. Regression multivariate analysis showed that total and sub-scales PPOS scores were only explained by the variable medical school. Both medical schools did not show any significant associations between socio-demographicvariables and total PPOS and its subscales scores. More patient- centered attitudes observed in the PBL medical school could be attributed to PBL methodology since both schools belong to the same University, are located in the same state of Brazil and differs basically in relation to their curricular models.